Assessing the impact of inertia and reactive power constraints in generation expansion planning. (15th December 2020) - Wogrin, S.; Tejada-Arango, D.; Delikaraoglou, S.; Botterud, A.
Abstract: On the path towards power systems with high renewable penetrations and ultimately carbon-neutral, more and more synchronous generation is being displaced by variable renewable generation that does not currently provide system inertia nor reactive power support. This could create serious issues of power system stability in the near future, and countries with high renewable penetrations such as Ireland are already facing these challenges. Therefore, this paper aims at answering the questions of whether and how explicitly including inertia and reactive power constraints in generation expansion planning would affect the optimal capacity mix of the power system of the future. Towards this end, we propose the novel Low-carbon Expansion Generation Optimization model, which explicitly accounts for: unit commitment constraints, Rate of Change of Frequency inertia requirements and virtual inertia provision, and, a second-order cone programming approximation of the AC power flow, accounting for reactive power constraints. An illustrative case study underlines that disregarding inertia and reactive power constraints in generation expansion planning can result in additional system cost, system infeasibilities, a distortion of optimal resource allocation and inability to reach established policy goals. Highlights: We propose a novel low-carbon expansion generation optimization (LEGO) model. LEGO factors in inertia and reactive power in generation expansion planning in a low-carbon power system. Disregarding inertia in planning can lead to infeasible capacity mix especially for high renewable targets. Disregarding reactive power in planning leads to distortions in the optimal allocation of resources. This can be fixed at a moderate cost, but may lead to less robust capacity mix.